ANALISIS DEFORMASI GEMPA LOMBOK 19 AGUSTUS 2018 BERDASARKAN DATA PENGAMATAN GPS KONTINU METODE STATIK - Pandika Adi Rahmadia, Muhamad
Lombok Island is surrounded by several earthquake sources, including the Back Arc Thrust Zone in the north, subduction zone in the south, and strike-slip faults on the west and east side. In 2018, there were four earthquakes with magnitudes above 6 occured on Lombok. Earthquakes can might cause surface deformation around the lombok island area. This deformation can be observed using static method of the Global Positioning System (GPS) technology. By conducting deformation research using GPS technology based on the campaign and InaCORS data, the magnitude and pattern of shifts displacements due to the Lombok earthquake could be obtained. The data is processed using Bernese 5.2 GNSS Software to obtain daily coordinates from each observation station. These results are used to obtain vectors and displacement patterns at each station. The results of horizontal displacement vectors show that the KDOO and PGRJ stations moved to northwest while the CMAT and MPGB stations moved to the northeast direction. The maximum value magnitude of displacement is 149 mm at KDOO while the minimum magnitude of displacement is 9 mm at CMAT. The horizontal movement of all stations tend to move northward that caused by the Indo-Australian Plate movement underneath Eurasian Plate Flores Back Arc Thrust. The vertical displacement results show that all the station were uplifted except MPGB. The biggest uplifting is 66 mm at KDOO and a 86 mm subsidence is observed at MPGB. Source of the earthquake that is being examined in this thesis was caused by the Flores Back Arc Thrust.